Finally, My Truth, by Me!: Why We Love and Live with Monsters - Alexander, Christine
Even now, all those years later since the shooting in November '95, when I hear someone else has been abused I still feel the shivers and the anger in my body from the abuse of 22 years, the feelings and memories never leave your body or your mind, they are always there! Five years were wasted in jail, and upon my freedom judges and lawyers did not want to know the truth. The only way to tell it was to "WRITE MY BOOK." We think we know the one we love, that he's a good person, humorous, helpful, and family comes first, BUT, friends and family are telling you otherwise, and you wonder why this is happening. Then there is your wedding and "BOOM," your whole world falls apart, they were right! Humour was sarcasm, strangers are helped, never family! He was not what he appeared to be. Then came the jail term, my lawyer sold me out, according to a judge I should have walked from the court house! At least my sons are alive, I would do it again in a second, no regrets!